Implementing Information Technology to Improve Public Service Quality: A Case Study of Loa Ipuh Darat Village, Kutai Kartanegara - Juliansyah; Saipul; Iman Surya (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study examines the implementation of information technology to improve the quality of public services in Loa Ipuh Darat Village by analyzing the effectiveness of the digitalization process using four policy implementation variables proposed by Edwards III: communication, resources, disposition, and bureaucratic structure. In addition, the study explores the supporting and inhibiting factors that influence the implementation of information technology in village-level public services. The objectives of this study are: (1) to describe and analyze the implementation of information technology in public services in Loa Ipuh Darat Village, Tenggarong District, Kutai Kartanegara Regency; and (2) to identify the supporting and inhibiting factors affecting its implementation. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, direct observation, and documentation. The interviews involved eight informants: the village head, the village secretary, two village administrative staff, one IT operator, two community members as service users, and one sub-district official. The study was conducted over three months, from March to May 2024. Data analysis followed the interactive model developed by Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The findings indicate that the implementation of information technology in public services has shown mixed results. Communication has been carried out hierarchically and relatively clearly, although continuous technical assistance is still needed. Resources remain the main constraint, particularly limited human resource competence, budget constraints, and inadequate IT facilities. The disposition of both village officials and the community is generally positive and adaptive, but disparities in digital literacy persist. The bureaucratic structure provides formal regulatory support; however, its effectiveness is limited by rigid administrative procedures and the absence of a specialized IT unit at the village level. Supporting factors include leadership commitment, positive attitudes among village officials, and the availability of initial network infrastructure. In contrast, inhibiting factors include limited technical competence, unstable internet connectivity, dependence on external technicians, and a less responsive bureaucracy. These findings highlight that successful digitalization in public services depends heavily on resource readiness, bureaucratic flexibility, and adequate infrastructure support.